Uji Aktivitas Antibakteri Formula Pasta Gigi Ekstrak Batang Karui (Harrisonia Perforata Merr.) Terhadap Bakteri Streptococcus Mutans - Wardatul Nurjannah; Yusriadi Yusriadi; Arsa Wahyu Nugrahani (Biology Department, Mathematics and natural science, Tadulako University, 2018)
Karui (Harrisonia perforata Merr.) is one of the many species that live in tropical regions such as Central Sulawesi (Palu) and has antibacterial activity. This research aims to find the variation effect of karui stem extract (Harrisonia perforata Merr.) in toothpaste towards stability of physical quality and antibacterial activity bacteria Streptococcus mutans. The concentrations of karui stem extract 1%, 2%, and 3% in toothpaste tested for antibacterial activity using pitting method which further tested for statistical analysis